2013
DOI: 10.1111/cei.12177
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-producing,ex-vivo-generated human tolerogenic dendritic cells induce the proliferation of immunosuppressive B lymphocytes

Abstract: SummaryWhile much is known about tolerogenic dendritic cell effects on forkhead box protein 3 (FoxP3) + regulatory T cells, virtually nothing is known about their effects on another arm of immunoregulation that is mediated by a subpopulation of immunosuppressive B cells. These cells suppress rheumatoid arthritis, lupus and inflammatory bowel disease in mice, and functional defects have been reported in human lupus. We show that co-stimulationimpaired tolerogenic dendritic cells that prevent and reverse type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 65 publications
2
53
0
1
Order By: Relevance
“…Although data regarding the effects on beta cell function and survival remain controversial [45,46], IL-6 may also stimulate beta cell repair. Thus, in DC-MSC combination therapy, multiple layers of tolerance could be formed involving regulatory DCs, T cells and even B cells [47] that may act and accumulate in relevant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although data regarding the effects on beta cell function and survival remain controversial [45,46], IL-6 may also stimulate beta cell repair. Thus, in DC-MSC combination therapy, multiple layers of tolerance could be formed involving regulatory DCs, T cells and even B cells [47] that may act and accumulate in relevant tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several mediators can induce Treg cell development including TGF-β and retinoic acid (RA) (Hall et al 2011;Caro et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Development of iTregs relies on several mediators including IL-12, TGF-β and RA (Hall et al 2011;Di Caro et al 2013). It has been observed that treating cell-cultured splenic DCs with RA and TGF-β significantly induced iTreg development , Di Caro et al 2013.…”
Section: Vitamin a And T Cellsmentioning
confidence: 99%
“…Development of iTregs relies on several mediators including IL-12, TGF-β and RA (Hall et al 2011;Di Caro et al 2013). It has been observed that treating cell-cultured splenic DCs with RA and TGF-β significantly induced iTreg development , Di Caro et al 2013. Retinoic acid also promotes the production of IL-10, which is essential for optimal action of Tregs (Wang et al 2007;Boks et al 2012).…”
Section: Vitamin a And T Cellsmentioning
confidence: 99%
See 1 more Smart Citation